The Effect of Experiential Marketing, Price Perception and Customer Satisfaction on Repurchase Intention in Somethinc Product Customers - Ningtyas , Arnistia Dwi; Paramitha, Dyah Ayu (Universitas Nusantara PGRI Kediri, 2025)
Research aim: The purpose of this study was to partially and simultaneously examine the effect of experiential marketing variables, price perceptions, and customer satisfaction on repurchase intentions for Somethinc products. Design/Method/Approach: This research utilizes a quantitative research methodology that focuses on establishing causal relationships. Primarydata was collected from 96 customers who use Somethinc products through a questionnaire (Google Form) given to respondents using a Likert scale, while secondary data was collected from various sources related to the object of research. The data was then processed using SPSS version 22 software. Research Finding: The results of this study empirically confirm that the three independent variables, namely experiential marketing, price perception, and customer satisfaction, together make a significant contribution to increasing consumer intention to repurchase Somethinc products. Theoretical contribution/Originality: This research can contribute to the understanding of the consumer decision-making process, especially in the context of purchasing personalized products such as beauty products. Practitionel/Policy implication: By implementing the practical and policy implications described above, Somethinc company can increase customer repurchase intention, strengthen brand position in the market, and achieve sustainable business growth. Research limitation: This study analyzes the relationship between experiential marketing, perceived price, and customer satisfaction as determinants of repurchase intentions in generation Z customers of Somethinc products.